Penataan Jalan Desa Melalui Program Penanaman Pohon dan Tanaman Hias di Sepanjang Jalan Poros Desa Wisata Masmas Kabupaten Lombok Tengah - Eva Febriani; Titi Laily Hajiriah (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2025)
The development of village road infrastructure is one of the important aspects in improving the quality of life of the community. The arrangement of village roads through a tree and ornamental plant planting program along the main road of Masmas Tourism Village aims to create a more beautiful and attractive environment. This program not only focuses on aesthetics, but also on the ecological benefits resulting from tree planting, such as improving air quality, reducing temperatures, and providing habitat for various species. This activity involves the active participation of the local community in the planning and implementation process, thereby increasing a sense of ownership and responsibility for the environment. In addition, planting ornamental plants is expected to attract tourists which in turn can improve the local economy. The methods used in this program include identifying strategic locations for planting, selecting appropriate types of trees and ornamental plants, and training for the community on how to care for plants. The results of this program are expected to provide long-term positive impacts, both in terms of the environment and socio-economics. Thus, the arrangement of village roads through this program is expected to be a model for other villages in an effort to create a better and more sustainable environment. This activity provides an overview of the importance of collaboration between the government, community, and related parties in realizing an environmentally friendly and competitive village.